Utilization of different habitats in Colobus angolensis palliatus in the forests of Diani Beach, Kenya - André, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
The Angolan black and white colobus monkey (Colobus angolensis palliatus) is an arboreal primate that inhabits coastal forest fragments on the south cost of Kenya and is consequently vulnerable to forest fragmentations. The study was carried out in March and April 2011 in Diani Beach in Kenya where two of the largest populations of the species are distributed. This study is a pilot study to test methods for a Master’s thesis. The aim was to investigate any variations in use of two habitats of C.a. palliatus and the forests of Diani Beach.